2015
DOI: 10.1039/c5ra12009h
|View full text |Cite
|
Sign up to set email alerts
|

Tannin as a gatekeeper of pH-responsive mesoporous silica nanoparticles for drug delivery

Abstract: Tannin grafted on mesoporous silica nanoparticles (tannin-MSNs) was synthesized by the amidation reaction of carboxyl benzyl borate with amino group modified MSN. Tannin-MSNs were an MCM-41 type of mesoporous material with a uniform diameter of about 150 nm. The XRD and N 2 adsorption/ desorption isotherm results demonstrated that the rhodamine was effectively loaded and the pores of MSN were blocked by tannin. Rhodamine as a model cargo was used to evaluate the loading and releasing behaviors of tannin-MSNs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Tannins as pH motifs were proved by the work of Hu and collaborators. Tannins, by the formation of boronate esters were found to modulate the release of the dye rhodamine at acidic pH [ 211 ].…”
Section: Applications Of Msns In Drug Deliverymentioning
confidence: 99%
“…Tannins as pH motifs were proved by the work of Hu and collaborators. Tannins, by the formation of boronate esters were found to modulate the release of the dye rhodamine at acidic pH [ 211 ].…”
Section: Applications Of Msns In Drug Deliverymentioning
confidence: 99%
“…With a gradually increase in studies, a series of MSN-based stimuli-responsive systems have been reported. 34,35 The drug release is subsequently to be triggered by environmental stimuli including physical signals (eg, temperature, 36,37 electricity, 38 magnetic field, 39 and photons [40][41][42] ) and chemical signals (eg, pH values, 43 redox potential, [44][45][46] and enzymatic activities 47,48 ). In this review, we intend to discuss about the advanced progress related to MSN for drug delivery associated with special focus on environmental responsive mechanisms and highlight the effect of endogenous stimuli in drug delivery such as pH, redox, enzyme, ATP, glucose, and H 2 O 2 , as well as exogenous stimuli including thermo, light, ultrasound, and magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the intercalation of the APS, the basal spacing of APSB was increased [27]. The copolymer hydrogel, AMCD can act as a "gate keeper" molecule in which it can be introduced to the tuning pore size of the clay for the effective loading and the controlled release of drug [28][29][30]. During the synthesis of AMCD from β-CD and AAm, CAN was used as the free radical initiator.…”
Section: Synthesis Of the Composite And Characterizationmentioning
confidence: 99%